ANALISIS PENGARUH GROSS PROFIT MARGIN(GPM),RETURN ON ASSET(ROA),DEBT TO EQUITY RASIO(DER) DAN NET PROFIT MARGIN(NPM) TERHADAP PERTUMBUHAN LABA PADA PT. SAT NUSA PERSADA TBK. - antin Yuliantin; kartin aprianti (STIE Wiyatamandala, 2022)
This research examines empirically the effect of Gross Profit Margin (GPM), Return On Aseet (ROA), Debt To Equty Ratio (DER), dan Net Profit Margin (NPM) to profit growth of companies PT. Sat Nusa Persada Tbk. The in this research this is all financial statements of PT. Sat Nusa Persada Tbk for 15 from 2007-2021, the sample used in this study was f10 years from 2011-2020. Sampling was conducted tusing purposive sampling. The analytical method used in this research is quantitative method, with classical assumption test, multiple linear regression, coefficient of determination and multiple correlation, hypothesis testing (T test) and simultaneous test (F test) with using tool of SPSS version 21. The result shows that Gross Profit Margin (GPM), Return On Asset (ROA) has no significant influence to profit growth, while Debt To Equity Ratio (DER), Net Profit Margin (NPM) has significant to profit growth in PT. Sat Nusa Persada Tbk. Based on the simultaneous test that Gross Profit Margin (GPM), Return On Asset (ROA), Debt to Equity Ratio (DER) dan Net Profit Margin (NPM) has a significant effect on profit growth in PT. Sat Nusa Persada Tbk.